PHYSICOCHEMICAL AND MICROBIAL ANALYSIS OF FECES FROM HORSES FED DIETS CONTAINING CITRUS PULP - Brandi, Roberta Ariboni; Tribucci, Adriana Moraes De Oliveira; Balieiro, Júlio César De Carvalho; Souza, Ricardo Luiz Moro De; Pereira, Alfredo Manuel Franco; Hoffman, Rhonda M. (Universidade Federal de Goiás, 2016)
Abstract This study aimed to evaluate the effect of diets containing increasing levels of citrus pulp on the physicochemical and microbiological characteristics of horses feces. Five mares, at an average age of 3.5 years old and body weight of 492 ± 44.5 kg were arranged in a 5 x 5 Latin Square. The experimental diet consisted of 60% coast-cross hay and 40 % of concentrate with increasing levels of citrus pulp (0, 7, 14, 21, and 28 %). To determine the fecal pH, samples were collected directly from the floor, immediately after defecation, in the first feces of the day at 07:00 a.m., and color and fecal consistency were evaluated. For microbiological analysis, an aliquot was reserved in plastic bags, frozen, and sent to the microbiological laboratory for further analysis. Lactic acid bacteria were counted for Lactobacillus spp. and Streptococcus spp. from fecal samples under anaerobic conditions. The diet produced differences (P<0.05) in feces consistency: 98% of the animals had normal and firm stools, while 2% were loose ruminant-type feces. We observed no difference (P<0.05) for color, verifying 100% of the animals of greenish feces, normal for equines. There was no effect (P>0.05) on pH and on the number of Lactobacillus spp. and Streptococcus spp. The inclusion of up to 28% citrus pulp concentrates for horses did not promote change in the physicochemical characteristics and on the population of lactic acid-producing bacteria in feces.

Resumo O presente estudo teve como objetivo avaliar o efeito de dietas com níveis crescentes de polpa cítrica nas análises físico-químicas e microbiológicas nas fezes de cavalos. Cinco éguas, com idade média de 3,5 anos e peso corporal de 492 ± 44.5 kg foram dispostas em um quadrado latino 5x5. As dietas experimentais consistiram de 60% de feno coast-cross e 40% de concentrado com níveis crescentes de polpa cítrica (0, 7, 14, 21, 28%). Para determinar o pH fecal foram colhidas amostras (diretamente do reto) das primeiras fezes do dia às 07:00 min e foram avaliados as características de cor e consistência fecal. Para as análises microbiológicas, um alíquota foi reservada em plásticos, congeladas e enviadas para o laboratório para posterior análise. As bactérias láticas foram enumeradas por Lactobacillus spp. e Streptococcus spp. a partir das amostras fecais, em condições anaeróbicas. Não houve efeito (P<0,05) para a consistência fecal, 98% dos animais apresentaram fezes normais e firmes, enquanto 2% apresentaram fezes do tipo soltas. Não houve diferença (P<0,05) para a cor sendo que 100% dos animais apresentaram fezes verdes e normais. Não houve efeito (P>0,05) no pH e no número de Lactobacillus spp. e Streptococcus spp. A inclusão de até 28% de polpa cítrica no concentrado para equinos não promove mudanças nas características físico-químicas e na população de bactérias produtoras de ácido lático nas fezes.
ANÁLISES FISICOQUÍMICAS E MICROBIOLÓGICAS DE FEZES DE EQUINOS ALIMENTADOS COM DIETAS QUE CONTÉM POLPA CÍTRICA
Keywords: byproducts; lactobacillus; nutrition; pH; lactobacillus; nutrição; pH; subprodutos